Dosimetry for small fields of high energy electrons using radiographic films - Bernui de Vivanco, Ma Giselle (2006)
In our institution there is a considerable amount of patients suffering skin carcinomas, for which, the treatment using small fields of high energy electronis a common option of treatment. The dosimetry using ionization chamber in small electron fields of high energy, according with the international protocols of dosimetry, requires of ionization chambers with special characteristics; equipment that our institution does not count; so it is necessary an alternative method to make these measurements. The linear behaviour of the electron films in energies greater than 250 keV; makes the film dosimetry one of the best options to make measurements in small electron fields of high energy; as much by its quality of results, information and low cost. The objective of this work is to provide to the Radiotherapy Department of the National Institute of Neoplasics Diseases a practical method, safe and economic to do the dosimetry of small electron fields of high energy; in a way that the international recommendations for dosimetry of electrons of high energy using film are applied considering the resources that are available, without implies that the quality of the results be affected in unfavourable form.